Development and validation of the Sources of Meaning in Life Scale for the Elderly in China. (2nd November 2021) - Zhou, Jing-Jing; Tong, Pei; Ren, Qing-Zhuo; Li, Ting; Zheng, Ya-Jing; Shen, Qiao-Qiao; Liang, Yun-Yi; Gao, Yu-Lin
Abstract: Objectives: People who find meaning in life can endure 'any' pain. However, there were no tools to investigate elderly individuals' sources of meaning in life in China. This study aimed to develop the Sources of Meaning in Life Scale for the Elderly (SMSE), and examine the validation and reliability in Chinese elderly. Methods: A 43-item pool of SMSE was formed by combining the preliminary interview and literature review. A cross-sectional survey of 627 elderly people was then conducted in two community health service centers, two hospitals, and two nursing homes in Guangzhou by the convenience sampling method. Test–retest reliability was assessed with 24 elderly persons. Results: Six dimensions, containing family (four items), social support (four items), value (seven items), life security (four items), personal development (four items), and leisure activity (five items) explained 62.16% of the variance in total. Confirmatory factor analysis model fitting indices were χ 2 = 694.652, df  = 330, χ 2 / df  = 2.105, SRMR = 0.0695, GFI = 0.853, IFI = 0.905, TLI = 0.889, CFI = 0.903, and RMSEA = 0.062. The Cronbach's alpha value of the scale was 0.924, while that of each dimension was between 0.727 and 0.870. The inter-class correlation (ICC) of the scale was 0.856. Conclusion: The SMSE has good reliability and validity that can be used to evaluate the sources of meaning and meaning in life for the elderly.